2018
DOI: 10.2967/jnumed.118.217745
|View full text |Cite
|
Sign up to set email alerts
|

64Cu-SARTATE PET Imaging of Patients with Neuroendocrine Tumors Demonstrates High Tumor Uptake and Retention, Potentially Allowing Prospective Dosimetry for Peptide Receptor Radionuclide Therapy

Abstract: http://jnm.snmjournals.org/content/60/6/777 This article and updated information are available at: http://jnm.snmjournals.org/site/subscriptions/online.xhtml Information about subscriptions to JNM can be found at: http://jnm.snmjournals.org/site/misc/permission.xhtml

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 23 publications
3
70
0
1
Order By: Relevance
“…As a complete image-based dosimetry tool, the algorithm has been employed in a variety of clinical studies for both therapeutic and diagnostic dose evaluation which have been used to inform patient management. [24][25][26][27] The overall residual error was observed to be comparable between iteratively optimized and tri-exponential algorithms, however, the VoMM method was shown to be most accurate at the early image phase with increasing error at later time points. This is to be anticipated as the observed activityand potential to influence sum of squared errorcarries less weight for the optimization task.…”
Section: Resultsmentioning
confidence: 99%
“…As a complete image-based dosimetry tool, the algorithm has been employed in a variety of clinical studies for both therapeutic and diagnostic dose evaluation which have been used to inform patient management. [24][25][26][27] The overall residual error was observed to be comparable between iteratively optimized and tri-exponential algorithms, however, the VoMM method was shown to be most accurate at the early image phase with increasing error at later time points. This is to be anticipated as the observed activityand potential to influence sum of squared errorcarries less weight for the optimization task.…”
Section: Resultsmentioning
confidence: 99%
“…A first-in-human retrospective study was recently conducted and seems to present same results than [ 64 Cu]-DOTATATE with high detection rate of suspected lesion associated to a high target-to-background contrast [ 123 ]. A recent first-in-human study also demonstrated potential interest for [ 64 Cu]-SARTATE analog [ 124 ].…”
Section: Targeting Of Somatostatin Receptors With Radiopharmaceutimentioning
confidence: 99%
“…The somatostatin receptor analogs are used to direct radionuclides for uptake by tumor cells, leading to death in a targeted fashion. Preliminary data using copper-64 labeled SARTATE suggests it can be safe and effective in neuroendocrine tumors (89). This radionuclide, and others including 177Lu-DOTA-Tyr3octreotate (Lutathera), are currently in trials for meningioma (NCT03936426, NCT03971461).…”
Section: Novel Approachesmentioning
confidence: 99%